MODL-38. DEVELOPMENTAL EFFECTS OF MYBL1 ACTIVATION ON MURINE BRAIN AND GLIAL DEVELOPMENT. (14th November 2022) - Azazmeh, Narmen; Rouleau, Cecile; Schoolcraft, Kate; Jacob, Etai; Malinowski, Seth; Busanovich, John P; Ramkissoon, Lori; Kang, Yun Jee; Ramkissoon, Shakti; Pelton, Kristine; Meng, Alice; Jones, Victor; et al.
Abstract: Low-grade gliomas (LGG) represent 30% of pediatric brain tumors. Their cellular origins are unknown but are presumed to arise from subtle alterations of progenitor cell cycle regulation during brain development. Rearrangements activating MYB and MYBL1 have been identified as drivers of LGG in angiocentric glioma and diffuse astrocytomas, respectively, but the roles of these genes in the normal brain and the development of LGG are poorly understood. We first performed a developmental analysis of human and mouse Mybl1 expression from bulk and single-cell RNA-sequencing and identified exclusive expression of MYBL1 in neural stem and progenitor cells in the ganglionic eminence. We also found that MYBL1 high cell transcriptomes are enriched in genes functionally involved in centromere and mitotic processes, strongly suggesting an association between MYBL1 expression and cellular proliferation states. We next hypothesized that C-terminal truncation may drive tumorigenesis through a direct increase in MYBL1 expression and cell proliferation. We developed a novel Cre-dependent knock-in mouse-model for human truncated MYBL1 expression and tested effects in oligodendroglial(Olig2-cre), astrocytic hGFAP-cre), and somatic(Ubiquitin-cre) cell types. In Ubq-cre:R26-MYBL1-tr mice there was expression and dysplasia in the salivary gland but no significant effects on brain development. In Olig2-Cre +/tg :R26-MYBL1-tr +/fl mice we observed higher susceptibility to motor seizures, early postnatal death without gross or microscopic abnormalities of brain morphology. In contrast, expression in stem cells and astrocytes of hGFAP-Cre +/tg :R26-MYBL1-tr +/fl mice drove dramatic abnormalities in brain development and altered proliferation of progenitor and stem cells, but not glioma formation. Single-cell RNA sequencing of MYBL1-tr cells from mNSCs and brains of mice were also used to determine patterns of altered expression driven by MYBL1-tr. These results indicate that aberrant MYBL1 activation affects neural stem/progenitor cell and brain development through altered cell proliferation. Future targeting of the pathways identified may be therapeutically beneficial for patients with LGG driven by MYB-family oncogenes.